Hepatic dysfunction in children with complicated malaria - Mannu, Alexander; Agarwalla, Sunil Kumar; Vasudevan, Jaishree; T., Kathir Subramaniam; A., Ahamed Basha (International Journal of Contemporary Pediatrics, 2018)
Background: Complicated malaria caused by Plasmodium falciparum alone or with P. vivax can lead to multi organ dysfunction. There is a paucity of studies about hepatic dysfunction in children with complicated malaria. Hence, this retrospective study was done to find out the clinico-biochemical profile of children with complicated malarial hepatic dysfunction from a malaria endemic region of India. Further, liver function test (LFT) response to Artemisinin-based combination therapy (ACT) i.e. artesunate + sulfadoxine-pyrimethamine therapy in the malarial hepatic dysfunction children was assessed. Methods: Out of 203 children confirmed to have malaria, 60 children were found to have complicated malaria with jaundice as per WHO malaria guidelines (total serum bilirubin >3 mg%). Physical examination, malaria related biochemical and ultra-sonographic findings were noted. All the children were found to be uniformly on ACT as per institute protocol adapted from WHO guidelines. Biochemical parameters of hepatic function were compared between day 1 and 4. Results: Presentations were fever, pallor and clinical jaundice in 100%, reddish urine in 63.3%, tender hepatomegaly in 100% and splenomegaly in 81.7% of the study population. Liver function test showed mild to moderate elevation of serum bilirubin and enzymes with remarkable recovery noticed with the use of ACT in all the study subjects. Conclusions: Clinical presentations of malarial hepatic dysfunction although mimics viral hepatitis, LFT showed mild to moderate elevation only. Further, ACT therapy was found effective in the management of all children with hepatic dysfunction in complicated malaria.